PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 67 PEMATANG PUDU KECAMATAN MANDAU - Aruan, Renni Dermawan; Syofni, Syofni; Hutapea, Nahor Murani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract:This research aims to improve the learning process and improve learning outcomes mathematicsin third grade students of SDN 67 Pematang Pudu by applying the model of Learning Direct. The subjects were third-grade students who have academic ability heterogeneous. This research is a class act with two cycles. Each cycle consisted of three meetings and one at each end of the cycle UH and has four stages, namely planning, implementation, observation and reflection. The results of observational studies showed the teachers and students sheets activities have done after the action. An increase in the number of students who achieved KKM in UH in the end of each cyclecompare to the number of students who achieve a score of KKM on base. The results of this study showed that the application of direct instructional model can improve the process of learning and improving learning outcomes mathematics in third grade students of SDN 67 Pematang Pudu Mandau District in the odd semester of the academic year 2013/2014.Â Keywords: Learning Process, Mathematics Learning Outcomes, Learning Direct, classroom action research